Effects of credit constraints on the productivity of small and medium-sized enterprises in Cameroon - Piabuo, S.M.; Baye, F.M.; Tieguhong, J.C. (Academic Journals, 2015)
This paper assesses the determinants and effects of credit constraints on the productivity of small and medium-sized enterprises (SMEs) in Cameroon. Use is made of the Cameroon enterprise survey data collected by the World Bank in 2009 and an endogenous switching regression model. Results show that interest rates, size of enterprise, size of loan, size of collateral, maturity of loans and legal status of enterprises are major sources of credit constraints faced by SMEs. Results also indicate that medium enterprises are more credit constrained than small enterprises; meanwhile the effects of credit constraints affect small enterprises more than medium enterprises. Credit constrained firms have lower levels of productivity relative to unconstrained firms. These results have implications for the creation of credit bureaux, prudential stringency and rationalization of the Cameroon tax system.